Characteristics of Body Dimension and Male Reproduction on Groups of Sheep Population at Pandeglang and Garut Regencies - Nataatmaja, DM; Arifin, J (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The objective of the research was to characterise body and testes dimension of sheep, the optimal age of scrotal development for selection, and the correlation between body and scrotal measurements as a base for selection. The sheep surveyed were those owned by farmers at Pandeglang and Garut regencies that have been received grants from various government projects (Banpres, Bansos, Bangub, APBD, APBN). Pandeglang area was predominated by local sheep and crosbred between local and Garut sheep. Garut area was predominated by Garut sheep and fighter sheep. Variables observed consisted of body weight, height at withers, scrotal circumference and scrotal length. Data were analysed using one-way analysis of variance continued with Duncanâs multiple range test by mean of SAS software release 6.04. Results showed that fighter sheep have higher body and scrotal dimensions than other breeds. Optimum level of development of scrotal for selection was achieved when the sheep aged one year. Only scrotal circumference and length could be used for assessing sheep fertility, whereas body measurement and scrotal dimensions has low correlation. (Animal Production 10(3): 140-146 (2008)Â Key Words: Scrotal circumference, scrotal length, sheep, fighter, selection